Factors Affecting Accounting Students In Choosing Accounting Career Path - Raharja, Surya; Liany, Dewi (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
This study aims to empirically examine factors that influence accounting students in choosing their career path.Ã‚Â The samples were 181Ã‚Â students from six biggest universities in Semarang, Indonesia.Ã‚Â Ã‚Â In this study,Ã‚Â data were collected using questionnaire survey and analyzed usingÃ‚Â multiple linear regression.Ã‚Â Ã‚Â The results of this study indicate that intrinsic motivation, extrinsic motivation, career exposure, and social values influence the career paths accounting student.Ã‚Â While third parties positively influence accounting students in determining career path butÃ‚Â it is not statistically significant. These findings may help us to understand how to improve career path among accounting students